KREATIVITAS GURU, PEMANFAATAN MEDIA PEMBELAJARAN DAN HASIL BELAJAR EKONOMI - M. Syaifullah Acc; Raden Gunawan Sudarmanto; Tedi Rusman (FKIP Unila, 2013)
Research is aimed to know whether there was an association between creativity in the teacher the learning process And utilization of media learning with study result of the economic. Methods used in research is a method of descriptive verifikatif with the approach ex post facto capital and survey. The result of research indicated that (1) A positive and significant relation exists between creativity in the teacher the learning process With students study result of the economic x first half of the class SMA Muhammadiyah 2 Bandarlampung lesson year 2012/2013. (2) A positive and significant relation exists between the utilization of media of learning With students study result of the economic x first half of the class SMA Muhammadiyah 2 Bandarlampung lesson year 2012/2013. (3) A positive and significant relation exists between creativity in the teacher the learning process and utilization of media of learning With students study result of the economic x first half of the class SMA Muhammadiyah 2 Bandarlampung lesson year 2012/2013. Keywords: creativity, learning media and achievement